Moving Beyond Trauma: Activating Resilience to Support Our Most Vulnerable Youth - JoAnne Malloy; Sara Manisco-Chapo (International Journal of School Social Work, 2024)
It is well-documented that exposure to toxic stress in childhood is associated with impaired social, emotional, behavioral, and neuro-biological development that often results in an inability to develop healthy relationships, learning difficulties, poor emotional regulation, and impaired problem-solving skills. Further, youth who grow up in unsafe environments or are subjected to structural inequality are faced with challenges over which they have no control. Using a positive, future-oriented, and trauma-responsive perspective while intentionally building resilience can effectively engage and support youth who have experienced toxic stress to overcome feelings of hopelessness and achieve positive outcomes. This paper includes a thematic analysis of semi-structured interviews with several youth who have experienced significant adversity as they participate in an intervention designed to support them to articulate, develop, and pursue their goals for transition from adolescence to adulthood. The paper includes a description of how systems and individualized interventions can build resilience, and the need for further research of the impact of relationship-based, person-centered approaches on the perspectives and outcomes of youth and young adults who have experienced significant trauma.
Keywords: trauma; resilience; MTSS; wraparound; RENEW; teacher-student relationships; school mental health; school social work